2014
DOI: 10.1111/jace.13422
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Diffraction from Levitated Solids Under Extreme Conditions—Structure and Thermal Expansion in the Eu2O3–ZrO2 System

Abstract: The accurate determination of structure and thermal expansion of refractory materials at temperatures above 1500°C is challenging. Here, for the first time, we demonstrate the ability to reliably refine the structure and thermal expansion coefficient of oxides at temperatures to 2200°C using in situ synchrotron diffraction coupled with aerodynamic levitation. Solid solutions in the Eu 2 O 3 -ZrO 2 binary system were investigated, including the high-temperature order-disorder transformation in Eu 2 Zr 2 O 7 . T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 42 publications
(51 reference statements)
1
22
1
Order By: Relevance
“…As the behavior of the thermal expansion coefficients calculated from the lattice constants for EZO of Maram et al 14) clearly disagreed with that in this work, the results of them are not shown in this figure. Similarly, the results of previous study 5) are not shown in this figure too.…”
Section: Resultscontrasting
confidence: 87%
See 2 more Smart Citations
“…As the behavior of the thermal expansion coefficients calculated from the lattice constants for EZO of Maram et al 14) clearly disagreed with that in this work, the results of them are not shown in this figure. Similarly, the results of previous study 5) are not shown in this figure too.…”
Section: Resultscontrasting
confidence: 87%
“…Figure 3 represents the temperature dependence of the lattice constants of EZO estimated from the Rietveld analyses. The results of Kutty et al, 18) Maram et al 14) and Hagiwara et al 5) are also shown in the figure for comparison. As compared with previous results, 5) the slope of EZO prepared in this work was larger than that.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…6) 1200°C. However, even in stoichiometric Eu zirconate sintered at 1300°C, the relative intensity of superstructure peaks was relatively low [18], while in [19] fully ordered europium zirconate was obtained after synthesis at 1400°C. In the present study, the temperature of additional heat treatment was 1450°C which is enough to form ordered pyrochlore from defected fluorite.…”
Section: Resultsmentioning
confidence: 92%
“…Rock Thermochemistry Laboratory at UC Davis to be used together with an existing 400 W CO 2 laser system, conventional aerodynamic levitator, CCD camera, and laser melting stage. Systems for laser melting of the powders and aerodynamic levitation are commercially available (Materials Development, Inc., Evanston, IL, USA) and employed at neutron and synchrotron sources for high‐temperature diffraction on melts and solids and will not be described in detail. The main components of the DnC are shown on Fig.…”
Section: Drop‐and‐catch Calorimeter Designmentioning
confidence: 99%